Зносостійкі покриття на алюмінієвих сплавах - Студент, М. М.; Маркович, С. І.; Гвоздецький, В. М.; Задорожна, Х. Р.; Сірак, Я. Я.; Кравчишин, Т. М.; Student, M.; Markovych, S.; Hvozdetskii, V.; Zadorozhna, K.; Sirak, Ya.; Кrаvchyshyn, T. (ЦНТУ, 2022)
Досліджено абразивну зносостійкість алюмінієвого сплаву Д16 з покриттями нанесеними методами: гальванічного хромування, надзвукового газополуменевого напилення (HVOF – High Velocity Oxygen Fuel Flame Spraying process), плазмо-електролітного оксидування, твердого анодування та електродугового напилення покриттів. Показано, що досліджені покриття підвищують абразивну зносостійкість алюмінієвого сплаву Д16 в 20...90 разів за умов випробовувань закріпленим абразивом та в 3...10 разів за умов випробовувань незакріпленим абразивом. Застосування цих методів підвищує зносостійкість деталей із алюмінієвих сплавів до рівня сталевих та дозволяє замінювати сталь і чавун на алюмінієві сплави із покриттями, щоб зменшити вагу деталей та викиди вуглецю в атмосферу. Aluminum alloys are widely used in industry. Recently, they are used as a replacement for steel for the manufacture of pulleys, gears, columns of hydraulic rotary transmissions of grabs, etc. This reduces the weight of the parts and reduces carbon emissions into the atmosphere. However, aluminum alloys have low abrasive wear resistance, so their use is possible with coatings on the surface. High-speed gas flame spraying (HVOF) was carried out on the equipment (Diamond Jet Hybrid gun). Arc coatings with a thickness of 500 µm were applied using FMI metallizer and FMI-2 powder wire (Cr6Al6B3Fe-base). PEO (oxido ceramic) coatings were synthesized on D16T aluminum alloy in an electrolyte of 3 g/l KOH + 2 g/l liquid glass (sodium silicate) with a pulsed current at a frequency of 50 Hz, with the ratio of the densities of the cathode and anode currents Jc/Ja+15/15 A /dm2. The duration of the PEO process is 60 min. The open porosity of the coatings was determined by the method of hydrostatic weighing. The phase composition of the surface layers was studied using a DRON-3.0 diffractometer. HVOF (VC) and PEO coatings have been found to have 3 to 4 times higher wear resistance than high carbon hardened steel 100Cr6 and 2 times higher than galvanic chromium coatings, but have high energy consumption. Two methods have the lowest energy consumption: electric arc spraying of coatings and hard anodizing. At the same time, the wear resistance of such coatings is significantly lower than that of coatings obtained by the PEO and HVOF (VC) methods. For the restoration of worn parts, the most appropriate methods are HVOF (VC) and electric arc spraying, as they allow applying thick coatings up to 5 mm. Conclusions: It was established that the studied HVOF (VC), PEO, EDP and hard anodized coatings significantly increase the abrasive wear resistance of aluminum alloy parts. HVOF (VC) and electric arc spraying methods can be used to protect new and worn parts from wear. PEO and hard anodizing methods can be used to protect against wear on new parts only. The use of these methods increases the wear resistance of parts made of aluminum alloys to the level of steel and allows replacing steel and cast iron with aluminum alloys with coatings, reducing the weight of parts and carbon emissions into the atmosphere.
Wear-resistant Coatings on Aluminum Alloys
Keywords: алюмінієвий сплав; гальванічне хромування; газополуменеве напилення; плазмо-електролітне оксидування; тверде анодування; електродугове напилення; aluminum alloy; galvanic chrome plating; gas flame spraying; plasma-electrolytic oxidation; hard anodizing; electric arc spraying